Helmholtz Portfolio Theme Large-Scale Data Management and Analysis (LSDMA) - Jung, Christopher [Hrsg.]Meyer, Jörg [Hrsg.]Streit, Achim [Hrsg.] (KIT Scientific Publishing, 2021)
The Helmholtz Association funded the ""Large-Scale Data Management and Analysis"" portfolio theme from 2012-2016. Four Helmholtz centres, six universities and another research institution in Germany joined to enable data-intensive science by optimising data life cycles in selected scientific communities. In our Data Life cycle Labs, data experts performed joint R&D together with scientific communities. The Data Services Integration Team focused on generic solutions applied by several communities.